Sensitivity Studies on the Impact of Dust and Aerosol Pollution Acting as Cloud Nucleating Aerosol on Orographic Precipitation in the Colorado River Basin - Vandana Jha; William R. Cotton; Gustavo G. Carrió; Robert Walko (Advances in Meteorology)
In this study, we examine the cumulative effect of pollution aerosol and dust acting as cloud nucleating aerosol;cloud condensation nuclei (CCN), giant cloud condensation nuclei, and ice nuclei (IN), on orographic precipitation in the Rocky Mountains. We analyze the results of sensitivity studies for specific cases in 2004-2005 winter season to analyze the relative impact of aerosol pollution and dust acting as CCN and IN on precipitation in the Colorado River Basin. Dust is varied from 3 to 10 times in the experiments, and the response is found to be nonmonotonic and depends on various environmental factors. The sensitivity studies show that adding dust in a wet system increases precipitation when IN effects are dominant. For a relatively dry system high concentrations of dust can result in overseeding the clouds and reductions in precipitation. However, when adding dust to a system with warmer cloud bases where drizzle formation is active, the response is nonmonotonic.